Alimentos, el estado y la economía mundial - McMichael, Philip (The International Journal of Sociology of Agriculture and Food, 1991)
The growing lilerature on the "internationalization" of agricultural and food systems has paid too little attention to the way in which the state itself not only sponsors this process, but is changed by it. ln most accounts of internationalization, the state (and state system) is taken as a given. This paper attempts to remedy this by offering a sketch of the world historical character of state-economy relations, across different periods of world capitalism. The goal is to stress that currently the transnationalization of the state is a key to the internationalization of agro-industrial food systems. ? Alimentos, el estado y la economía mundial Resumen ?La creciente literatura sobre la "internacionalización" de los sistemas agrícola y alimentario ha prestado poca atención a la manera como el Estado, no sólo ha sido responsable de dicho proceso, sino que al mismo tiempo, también es cambiado por é. En la mayoría de las consideraciones sobre la internacionalizacíon, el Estado (y el sistema estatal) se asume tal como este se presenta. Este trabajo analiza el carácter histórico mundial de las relaciones Economía-Estado a través de diferentes períodos del desarrollo capitalista. Su objetivo es resaltar que la actual transnacionalización del Estado es una clave de la internacionalización de los sistemas alimentarios agroindustriales.